SISTEM INFORMASI E-SHOP PENJUALAN BARANG FASHION BERBASIS WEB (STUDI KASUS : AFROW)indonesia - Zikri, Achmad; Marhaeni, Marhaeni (JURNAL REKAYASA INFORMASI, 2024)
Afrow is a clothing (brand) that operates in the field of fashion sales. In the sales process, Afrow still has problems in marketing and promoting its products, because currently Afrow only carries out marketing and promotions through Tokopedia and Shopee. With a personal website (e-shop), it is easy to do branding. In 2021, affrow sales will be much reduced compared to the previous year. This research aims to design and build a web-based e-shop information system to facilitate the sales process and increase affrow sales. The system development method uses Extreme Programming. Modeling using UML. Data collection used interview, o bservation and literature study methods. This research produces a web-based e-shop goods sales information system that can record goods transactions and produce online reports and provide real- time information so as to minimize errors caused by human factors and facilitate the process of selling and purchasing goods. , fast, transparent and has better mobility and flexibility. Kata Kunci : Information System, E-Shop, Extreme Programming